MOTIVATIONAL ORIENTATION OF CROSS-MAJOR GRADUATE ENGLISH STUDENTS IN LEARNING ENGLISH AT MULAWARMAN UNIVERSITY - Saphan, Serry; Iswari , Weningtyas Parama; Suhatmady , Bibit (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study aimed to investigate the kinds of motivation in learning English of the cross-major graduate English students at Mulawarman University. This study used a case study as a research approach in qualitative methods to analyze the data. The study involved four ctoss-major graduate students of English study program in Mulawarman University. The researcher found the students’ motivation to learn English because of the existence of their motivation by delivering the interviews. Results of the study shows there are four students had motivation in learning English consists of one student had amotivation in learning English at study program of English education in Mulawarman University. This involved three kinds of motivation: intrinsic, extrinsic, and amotivation. Finally, it was suggested that the students who learn English should be aware of their own motivation in learning English so they can achieve their goals and they should prepared and decided what they want to be in the future with their English knowledge. Moreover, the future researchers can conduct the study about students’ motivation in learning English with other theories in other schools and universities.